Photo-painting: iconographic sources, image and forgetting memory - Mariano, Erika (Revista do Colóquio, 2021)
The article examines the representations of a specific type of image production, photophotography. From it, the production of meanings in photography, through a discussion about the modes of creation, memory and authorship. These images require the context of an entire historical period. Who photographed? Who touched up? Where was it done? The example of its iconographic source is not secondary to an original document written. Craft that is part of Brazilian culture, forgotten in a brief and trivial erasure of historical memories.
Keywords: Photo-painting; memory; authorship; iconography